Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To simplify the expression [tex]\( 3 \sqrt{50} + 2 \sqrt{45} - \sqrt{2} + \sqrt{5} \)[/tex], follow these steps:
1. Simplify the square roots individually:
- [tex]\( \sqrt{50} = \sqrt{25 \times 2} = \sqrt{25} \times \sqrt{2} = 5 \sqrt{2} \)[/tex]
- [tex]\( \sqrt{45} = \sqrt{9 \times 5} = \sqrt{9} \times \sqrt{5} = 3 \sqrt{5} \)[/tex]
- [tex]\( \sqrt{2} \)[/tex] remains [tex]\( \sqrt{2} \)[/tex]
- [tex]\( \sqrt{5} \)[/tex] remains [tex]\( \sqrt{5} \)[/tex]
2. Substitute these simplified square roots back into the expression:
- [tex]\( 3 \sqrt{50} = 3 \times 5 \sqrt{2} = 15 \sqrt{2} \)[/tex]
- [tex]\( 2 \sqrt{45} = 2 \times 3 \sqrt{5} = 6 \sqrt{5} \)[/tex]
Thus, the expression now becomes:
[tex]\[ 15 \sqrt{2} + 6 \sqrt{5} - \sqrt{2} + \sqrt{5} \][/tex]
3. Combine like terms:
- Combine the [tex]\(\sqrt{2}\)[/tex] terms: [tex]\( 15 \sqrt{2} - \sqrt{2} = (15 - 1) \sqrt{2} = 14 \sqrt{2} \)[/tex]
- Combine the [tex]\(\sqrt{5}\)[/tex] terms: [tex]\( 6 \sqrt{5} + \sqrt{5} = (6 + 1) \sqrt{5} = 7 \sqrt{5} \)[/tex]
4. Write the final simplified expression:
The simplified expression is:
[tex]\[ 7 \sqrt{5} + 14 \sqrt{2} \][/tex]
Hence, [tex]\( 3 \sqrt{50} + 2 \sqrt{45} - \sqrt{2} + \sqrt{5} \)[/tex] simplifies to [tex]\( 7 \sqrt{5} + 14 \sqrt{2} \)[/tex].
1. Simplify the square roots individually:
- [tex]\( \sqrt{50} = \sqrt{25 \times 2} = \sqrt{25} \times \sqrt{2} = 5 \sqrt{2} \)[/tex]
- [tex]\( \sqrt{45} = \sqrt{9 \times 5} = \sqrt{9} \times \sqrt{5} = 3 \sqrt{5} \)[/tex]
- [tex]\( \sqrt{2} \)[/tex] remains [tex]\( \sqrt{2} \)[/tex]
- [tex]\( \sqrt{5} \)[/tex] remains [tex]\( \sqrt{5} \)[/tex]
2. Substitute these simplified square roots back into the expression:
- [tex]\( 3 \sqrt{50} = 3 \times 5 \sqrt{2} = 15 \sqrt{2} \)[/tex]
- [tex]\( 2 \sqrt{45} = 2 \times 3 \sqrt{5} = 6 \sqrt{5} \)[/tex]
Thus, the expression now becomes:
[tex]\[ 15 \sqrt{2} + 6 \sqrt{5} - \sqrt{2} + \sqrt{5} \][/tex]
3. Combine like terms:
- Combine the [tex]\(\sqrt{2}\)[/tex] terms: [tex]\( 15 \sqrt{2} - \sqrt{2} = (15 - 1) \sqrt{2} = 14 \sqrt{2} \)[/tex]
- Combine the [tex]\(\sqrt{5}\)[/tex] terms: [tex]\( 6 \sqrt{5} + \sqrt{5} = (6 + 1) \sqrt{5} = 7 \sqrt{5} \)[/tex]
4. Write the final simplified expression:
The simplified expression is:
[tex]\[ 7 \sqrt{5} + 14 \sqrt{2} \][/tex]
Hence, [tex]\( 3 \sqrt{50} + 2 \sqrt{45} - \sqrt{2} + \sqrt{5} \)[/tex] simplifies to [tex]\( 7 \sqrt{5} + 14 \sqrt{2} \)[/tex].
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.